Indirect pulp capping using different calcium hydroxide products: A clinical study - Kuzmanović-Radman Irena; Đeri Aleksandra; Arbutina Adriana; Janković Ognjenka; Josipović Renata; Knežević Nataša (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Indirect pulp capping is a therapeutic intervention in the treatment of deep carious lesion in order to stimulate odontoblasts to produce tertiary dentin using different biomaterials based mainly on calcium hydroxide. The aim of this study was to assess the effect of hard-setting (Dycal) and a suspension of calcium hydroxide (Calcipulp) in the treatment of deep carious lesion (caries profunda). Materials and Methods. Clinical study included 29 patients of both genders, age 16 to 40, and 45 teeth of different morphological groups with verified caries profunda using clinical and radiographic examination. After the cavity preparation, calcium hydroxide materials (Dycal or Calcipulp) were applied on the pulpal wall and cavities temporarily restored (phosphate cement) for the period of two months. After this period cavities were restored with composite materials and clinically observed during twelve months, with mandatory check-ups after three and six months. Results. Obtained results showed that indirect pulp capping using calcium hydroxide suspension (90.0%) was more successful than hard-setting material (84.0%), but with no statistically significant difference. Conclusion. Suspension and hard-setting calcium hydroxide were equally successful in the treatment of caries profunda.